2015
DOI: 10.1080/10810730.2015.1018638
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Health-Related Quality of Life Among a Population-Based Sample of Cancer Patients

Abstract: Health-related quality of life (HRQOL) is an important outcome in cancer care. Few studies indicate that that health literacy (HL) influences cancer patients’ HRQOL, but additional investigation is needed. We examined the relation between HL and HRQOL among cancer patients. A cross-sectional survey was conducted with cancer patients in Wisconsin during 2006–2007. Data on sociodemographics, clinical characteristics, HRQOL, and HL were obtained from the state’s cancer registry and a mailed questionnaire. Regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 49 publications
9
98
1
7
Order By: Relevance
“…In this study, health literacy and HRQoL means ranked higher in PCI patients with 10.72 scores and 43.89 scores, respectively. Similarly (Halverson et al, 2015), the higher levels of health literacy positively influenced HRQoL scores in PCI patients. Also, given that general health perception is among the important independent determinants of health service utilization (Lam, Fong, Lauder, & Lam, 2002), a higher HRQoL is likely to increase individual health behaviors and selfcare management for PCI patients after discharge.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, health literacy and HRQoL means ranked higher in PCI patients with 10.72 scores and 43.89 scores, respectively. Similarly (Halverson et al, 2015), the higher levels of health literacy positively influenced HRQoL scores in PCI patients. Also, given that general health perception is among the important independent determinants of health service utilization (Lam, Fong, Lauder, & Lam, 2002), a higher HRQoL is likely to increase individual health behaviors and selfcare management for PCI patients after discharge.…”
Section: Discussionmentioning
confidence: 88%
“…Recent reports have shown that health literacy is now emerging as a significant determinant to improving HRQoL in patients with coronary artery disease (Halverson et al, 2015). In particular, in PCI patients, health literacy could play a key role in reinforcing medication knowledge or medication adherence because the high-risk population after PCI requires a relatively high number of prescriptions for medication for the medical therapy after discharge (Reuter et al, 2015).…”
Section: Purposementioning
confidence: 99%
“…By contrast, Halverson et al. () reported that health literacy is a very influential factor in health‐related quality of life among patients with cancer. Our study also showed that better health literacy was related with higher health‐related quality of life.…”
Section: Discussionmentioning
confidence: 93%
“…However, these studies failed to find a significant relationship between health literacy and health-related quality of life. By contrast, Halverson et al (2015) reported that health literacy is a very influential factor in health-related quality of life among patients with cancer. Our study also showed that better health literacy was related with higher health-related quality of life.…”
Section: Participants With Better Medication Adherence Had Highermentioning
confidence: 94%
“…Predictors of interest included: age at diagnosis, ethnicity/race (white vs. other), number of relatives (mother, sisters, daughters, grandmothers, and aunts) with a history of breast cancer, education (at least a college degree vs. no college degree), household income ($ midpoints of income categories), type of treatment (breast‐conserving surgery or unilateral mastectomy vs. bilateral mastectomy), type of health insurance (private/employer/spouse/other insurance vs. Medicaid/Medicare vs. none), and urbanicity (Metropolitan vs. non‐metropolitan RUCA codes) . Health literacy was measured as the cumulative score across five questions rated on a five‐point Likert scale …”
Section: Methodsmentioning
confidence: 72%